Konsep Learning Community Dalam Merdeka Belajar Menurut Al-Qur’an Surat Al-Kahfi Ayat 10-15 Kajian Ilmu Pendidikan Islam - Wahidah, Evita Yuliatul; Hidayati, Ismah (STAI Al-Musaddadiyah Garut, 2024)
In the pursuit of cultivating quality human beings, education plays an indispensable role. As beings endowed with immense potential by Allah SWT, it is our duty to continually evolve with the times while adhering to Islamic values. This principle applies to the continuous development and innovation in education and learning processes. An example of such educational advancement, which is either about to be implemented or already practiced in some schools and higher education institutions in Indonesia, is the